“...Non-devoutness of the Present Age...” Transformations of Godliness in the 2nd Half of the 19th Century (Theatrum historiae, 2011)
This paper tries to describe the transformations of godliness in the second half of the 19th century in the way that it was reflected by Catholic priests who were in daily contact with believers of all social groups in towns and villages. The main source of information are articles published in “Časopis katolického duchovenstva” (“Magazine of the Catholic Clergy”) and in “Pastýř duchovní” (“The Pastor”). The advantage of these sources is main- ly the fact that in a periodical, which was published regularly, contributors responded to the social climate quite currently and in this way they succeeded in capturing a number of phenomena illustrating the transformation of godliness of the majority population. During the “long” 19th century, in these periodicals, we could find more than twenty contributions concerning this problem directly and a lot of other ones dealing with this topic marginally, especially in connection with pastoral work, teaching religion at schools, raising children and young people in families, churchgoing, confessing, Holy Communion and celebrating religious holidays. The objective of the paper is to find the answer to the question of how the concept of “non-devoutness” was defined by Catholic priests themselves, and what it meant exactly in their interpretation and what its manifestations were. The French Revolution and its influence, which fatally spread to other European countries and was followed by the reform activities of Austrian rulers, especially Joseph II, was traditionally regarded as the beginning of this process. The writers mentioned specific, constantly repeating and strengthening phenomena which showed the godlessness of the majority population. Above all, it was a very half-hearted approach to religious education in the family which planted the seeds of shallow faith. In addition, teaching of religion at schools often lagged behind the determined ideal. The cause was not only lax school atten- dance, but also the difficult situation of catechists both in terms of salary and in terms of their position in the teaching staff. Many catechists were also notably limited by their own abilities to lead classwork; moreover, there was no unified curriculum for teaching cate- chism. In the third quarter of the 19th century, religious education at higher secondary schools and secondary schools was cancelled, which did not contribute to education of godliness either. The godliness of an adult believer was marked by not quite a satisfactory situation in the family and in the education system. The control over believers was entirely in the hands of parish priests, who had to fight against numerous obstacles, however. It was very hard for them to keep track of their parishioners who lived in towns, especially in emerging workers’ settlements, where, due to large fluctuation and anonymity of believers, it was not within priests’ powers to have an awareness of all their flock. Parish priests mostly focused on insufficient churchgoing and neglecting confession, Holy Communion and observing festive days. The observance of Sunday as a feast day, which is reserved for contemplation, was disturbed by a number of things starting from the fact that it was common that believers worked on a festive day, amused themselves, held drinking bouts or they just did not go to church services and ceremonies at all, alleging miscellaneous, sometimes almost quaint, reasons of their absence. Priests used all possible available means to reform their believers. Most often, priests reasoned with them, criticised their offences at the confession, held afternoon Christian exercises eagerly, tried to prepare interesting and attractive sermons and established Christian societies. However, at the end of the century more and more often, priests met coldness and indifference of believers and so-called “register Catholicism”, which meant that many Catholics were baptized, but for miscellaneous reasons they refused to comply with the demands of their Church for a godly life or they were entirely indifferent to this problem.